Validity and reproducibility of foot motion analysis using a stretch strain sensor - Sakamoto, Kodai; Tsujioka, Chie; Sasaki, Megumi; Miyashita, Toshinori; Kitano, Masashi; Kudo, Shintarou (Gait & posture, 2021)
•The foot motion analysis method using the wearable system is proposed.•The Proposed system was compared to a multi-segment foot model.•This system has the capability to reflect foot motion.•This system may assess foot kinematics while wearing the shoe. Multi-segment foot analysis is traditionally challenging to perform while subjects are wearing footwear or a foot orthosis and is difficult to apply in the clinical setting. A recently developed stretch strain sensor (STR), that is thin and highly flexible, may solve this limitation because it does not require observation using a camera and is highly portable. This study aimed to examine the reproducibility and validity of foot motion analysis using the STR during walking and running by comparing it with a conventional motion capture system. Twenty-one healthy participants were examined in this study. The STR was placed on the participant's foot in one of two locations in separate experiments (spring ligament; SL and navicular drop; ND methods). Foot kinematic data during walking and running were simultaneously recorded using the STR and a three-dimensional motion capture system. Intra-class correlation (ICC) was used to assess test-retest reproducibility of the STR method. Cross-correlation coefficient evaluated the similarity of the pattern of the signals between the two systems. Pearson and Spearman correlation analysis was used to evaluate the relationships between the STR measurement and angular excursion of the forefoot or hindfoot. The ICCs of the SL method were 0.95 and 0.96, and those of the ND method were 0.93 and 0.71 during walking and running, respectively. In the SL method, the pattern of the signals between the STR and forefoot frontal motion was strongly correlated. The STR measurement was significantly correlated with forefoot eversion excursion (walking: r=-0.67, running: r=-0.64, p < 0.01 each). In the ND method, the STR signal was not associated with forefoot and hindfoot kinematics. Our results showed that the STR has acceptable reproducibility and validity of foot motion analysis. This system may enable measurement of foot motion while subjects are wearing shoes and outside the laboratory.